El nivel de educación de los padres y madres de familia y su incidencia en el rendimiento escolar de los niños y niñas de la escuela Sósena Barrezueta de Zamora de la parroquia la providencia, del cantón Machala, provincia de El Oro periodo lectivo 2012-2013 - Villacrés Pauta, Paola Diliana (2013)
Faced with the great challenges of transformation and economic, political, social, technological and cultural development, education should not be left behind, the process that has been used to carry out this project of a continuous design of bibliographic information collection, Strategies Which guide the development of this document.